Improving Radio Frequency Transmission Properties of Graphene via Carrier Concentration Control toward High Frequency Transmission Line Applications. (8th February 2019) - Yang, Jae Hoon; Yang, Hyoung Woo; Jun, Byoung Ok; Shin, Jeong Hee; Kim, Seunguk; Jang, A‐Rang; Yoon, Seong In; Shin, Hyeon Suk; Park, Deoksoo; Park, Kyungho; Yoon, Duhee; Sohn, Jung Inn; et al.
Abstract: Graphene has been gradually studied as a high‐frequency transmission line material owing to high carrier mobility with frequency independence up to a few THz. However, the graphene‐based transmission lines have poor conductivity due to their low carrier concentration. Here, it is observed that the radio frequency (RF) transmission performance could be severely hampered by the defect‐induced scattering, even though the carrier concentration is increased. As a possible solution, the deposition of the amorphous carbon on the graphene is studied in the high‐frequency region up to 110 GHz. The DC resistance is reduced by as much as 60%, and the RF transmission property is also enhanced by 3 dB. Also, the amorphous carbon covered graphene shows stable performance under a harsh environment. These results prove that the carrier concentration control is an effective and a facile method to improve the transmission performance of graphene. It opens up the possibilities of using graphene as interconnects in the ultrahigh‐frequency region. Abstract : The radio frequency (RF) transmission properties of graphene are improved by amorphous carbon deposition . Amorphous carbon can increase the carrier concentrations of graphene without any degradation of the electrical performance of graphene. The enhanced RF transmission performance of graphene in this study shows the highest RF signal transmission performance in a single layer of graphene.